Diversity of Arthropods in Soybean Crops (Glycine max L. Merill) with Insecticidal Treatment - Madjidi, Madjidi; Ramadhan, Tris Haris; Syahputra, Edy (Jurnal Sains Mahasiswa Pertanian, 2018)
ABSRTACTOne of the main obstacles to increasing soybean production is the presence of pest attacks that can reduce yields by up to 80%. Efforts to control pests on soybean plants are generally still rely on the application of synthetic insecticides in a way that is not wise, resulting in negative impacts for agroecosystems, especially the decline in arthropod diversity that plays a role in maintaining the stability of ecosystems against pest attacks. The purpose of this study is to explore the level of diversity and the presence of arthropods in insecticide controlled soybean crops. The study was conducted in Rasau Jaya 2 sub-district, Kubu Raya District, and Plant Pest Laboratory of Agriculture Faculty of Tanjungpura University for 4 months from June to September 2017. This study used Randomized Block Design consisting of 2 types of insecticide treatment with 4 replications that is insecticide Sipermetrin (0.25 ml/l, 0.50 ml/l, 0.75 ml/l, 1.00 ml/l of concentrations) and Profenofos (0.25 ml/l, 0.50 ml/l, 0.75 ml/l, 1.00 ml/l, 1.50 ml/l, and 2.00 ml/l of concentrations). The results showed that in general the diversity of arthropods in soybean plants was high, with total arthropods found as many as 3,297 individuals, 9 orders, 53 families, and 89 species. The highest decrease of diversity after application was found in the treatment of insecticide containing Sipermetrin with concentration 0.50 ml/l with value of H '= 2,085 and Profenofos with concentration 1.00 ml/l with value H' = 2,135.Â Keywords: Arthropod Diversity, Insecticide, Pest Attack.